Differing Susceptibilities of Platelets from Normal Individuals and Patients with von Willebrand’s Disease to Attack by Quinine- and Quinidine-Dependent Antiplatelet Antibodies - Pfueller, Sharron L; Bilston, Robyn A; Logan, Dana; David, Rosemary; Sloan, Ian G; Firkin, Barry G (Thrombosis and Haemostasis, 1989)
Reactivity of quinine- and quinidine-dependent antiplatelet antibodies has been compared in platelet-rich-plasma (PRP) from normal donors and from patients with von Willebrand’s disease (vWd). One quinine-dependent antibody (Q. Ab) caused platelet aggregation and [14C] serotonin release with only 7 of 12 normal donors, while another Q. Ab and a quinidine-dependent antibody (Qd. Ab) caused aggregation and release with all 12. Drug- dependent IgG binding and PF 3 availability induced by the antibodies were, however, comparable in all donors. Differences in responsiveness were associated with platelets and not plasma. vWd platelets showed normal drug-dependent IgG binding, but decreased aggregation and serotonin release to most drug- dependent antibodies. Responsiveness was not restored by purified vWf:Ag, but, in one case, was corrected by normal plasma or cryoprecipitate. Drug-dependent binding of the Q. Ab which caused variable responsiveness in normals was to the same platelet antigens (GPIb and GPIIIa) in both normal and vWd platelets and did not require plasma components. Reduced PF 3 availability was seen with some antibodies in some vWd patients. Plasma from two of these patients inhibited aggregation of normal platelets to Q. Ab and one of these inhibited aggregation to ADP. Antiplatelet antibodies were detected in these two plasmas by ELISA. Thus some Q. Ab produce different responses with platelets from different donors. In vWd, reduced responsiveness to Q.Ab and Qd. Ab may result from production of inhibitory antiplatelet antibodies.
Keywords: Platelets; Thrombocytopenia; Drug-dependent antibodies; von Willebrand’s disease; Quinine